The importance of report analysis in ensuring the effectiveness of financial decisions - Dzhumaeva Gul rukh Dzhurakulovna (THE INNOVATION ECONOMY, 2026)
This article presents a statement of views and considerations on the theoretical aspects of the role and significance of accounting and reporting as important factors in achieving efficiency in financial decision-making, the importance of their analysis on a scientific basis.